Potential markets for forage hybrids in East Africa - Junca Paredes, Jhon Jairo; Flórez, Jesús Fernando; Enciso, Karen; Hernández, Luis Miguel; Triana Ángel, Natalia; Burkart, Stefan (International Center for Tropical Agriculture, 2023)
Both low quantity and quality of forage limits the development of the cattle sector in East Africa. New forage hybrids developed for the region are a promising effective response to these difficulties because of their adaptability to the local soil and climate conditions and response to pests and diseases. In addition, they contribute to reducing methane emissions and use nitrogen more efficiently, which translates into a reduced use of chemical fertilizers, cost savings, and mitigation of greenhouse gas emissions. The aim of this study was to estimate the size and values of potential markets for new interspecific Urochloa and Megathyrsus maximus hybrids for East Africa (and partially West Africa). In methodology, first, the forage hybrid market segments were described. Second, forage requirements for feeding the national cattle herds were determined and the area required to produce the forages were defined based on secondary data from the FAO and expert consultation. Third, based on existing information from a study that defined potential geographical suitability for the hybrids of interest in the region, the size of the potential market for the two materials was determined. Fourth, the commercial values of the potential markets were defined using geometric averages for market prices. The analysis includes several countries in eastern and western Africa, namely Ethiopia, Kenya, South Sudan, Tanzania, Uganda, Nigeria, and Mali. Results shows that there is a potential market with a value of US$174,665,945 for new interspecific Urochloa and Megathyrsus maximus hybrids in the analyzed countries. Market possibilities for forage hybrid seeds were identified. However, a legal and economic framework is required to facilitate adoption. As well as an accompaniment of extension services that promote the sustainability of these technologies over time.